PENGARUH KOMPETENSI KEPALA DESA TERHADAP KEBERHASILAN PEMBANGUNAN DESA DI KECMATAN SAHU TIMUR - Beno, Fendy; Rumapea, Patar; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract : Leave from early watch result that Interest carries the wind Village at Sahu's district East mostindication stills was optimal at impersonate so still a lot of Development at silvan ones haven't prepalent.Thus, this research intent to know how Interest influence carries the wind Village to Silvan Developmentsuccess at district Sahu East.This research gets eksploratif's character, with quantitative approaching. gathered file passthrough kuesioner's instrument that is broadcast to 40 district society respondents Sahu East that assesswalking Development at each Village. Collected data then at analisis utilizes analisis's tech linearregression and analisis is simple correlation.Point out observational result that carries the wind Village still was optimal, so can't yet pushSilvan Development success.Influential Silvan head to Silvan Development success that is at Sahu's district East. Suggestedthat more Silvan head increase Interest quality so can push Village Development at Sahu's district East.Key word: Interest carries the wind Village, Silvan Development success